2021
DOI: 10.1002/lno.11876
|View full text |Cite
|
Sign up to set email alerts
|

Decreased calcium concentration interferes with life history defense strategies of Ceriodaphnia cornuta in response to fish kairomone

Abstract: Declining calcium in freshwater lakes has become a serious threat to aquatic organisms, which may affect the anti‐fish defense of cladocerans with high calcium demand. To evaluate the effects of low calcium on life history strategies of cladocerans for defending against fish predation, we exposed Ceriodaphnia cornuta to eight concentrations of calcium ranging from 0.5 to 50.0 mg L−1 in the absence and presence of fish kairomone, and observed the changes in body surface, recorded the key life‐history traits, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Our results showed that the high concentration of atrazine caused the decrease of individual dry weight of D. pulex, but as the concentration selected in this experiment was limited, thus the critical concentration of atrazine that causes the reduction of individual dry weight cannot be obtained. Previous studies concluded that fish predation kairomone attenuates the adverse effects of environmental stressors on the growth and reproduction of cladocerans (Robison et al, 2018;Gu et al, 2020b;Huang et al, 2021), and the results of our experiment demonstrated for the first time that the fish predation kairomone attenuated the negative effects of atrazine on several population traits. These results indicated that fish kairomone can alleviate the stress ability of cladocerans.…”
Section: Discussionsupporting
confidence: 72%
“…Our results showed that the high concentration of atrazine caused the decrease of individual dry weight of D. pulex, but as the concentration selected in this experiment was limited, thus the critical concentration of atrazine that causes the reduction of individual dry weight cannot be obtained. Previous studies concluded that fish predation kairomone attenuates the adverse effects of environmental stressors on the growth and reproduction of cladocerans (Robison et al, 2018;Gu et al, 2020b;Huang et al, 2021), and the results of our experiment demonstrated for the first time that the fish predation kairomone attenuated the negative effects of atrazine on several population traits. These results indicated that fish kairomone can alleviate the stress ability of cladocerans.…”
Section: Discussionsupporting
confidence: 72%
“…Speci cally, we used two predictive functions to t the data. An exponential rise to an asymptote function, y = J max (1-e -pt ), was used to t the relationships between D. magna body size and growth days at presence or absence of sh kairomone, where y is body size of D. magna at time t, J max is the predicted asymptotes of the exponential rise functions (maximum value) when t approaches in nity, and p describes the initial rate of change in the response [45]. An exponential decline to an asymptote function, y = L min + αe -rt , was used to t the relationships between spine length / body size of D. magna and growth days at presence or absence of sh kairomone, where y is spine length / body size of D. magna at time t, L min is the predicted asymptotes of the exponential decline functions (minimum value) when t approaches in nity, and r describes the initial rate of change in the response [48].…”
Section: Discussionmentioning
confidence: 99%
“…We set up the experiments in the absence (control) and presence (treatment) of sh kairomone. The stocked sh kairomone was diluted 20 times in the COMBO medium to produce the target concentration (one sh per 10 L), as detailedly described in Huang et al [45]. Each treatment or control contained 250 replicates, and each replicate containing one individual was cultured in 50 mL of the COMBO medium with the green alga S. obliquus as food (1.5 mg C L −1 ).…”
Section: Experimental Designmentioning
confidence: 99%
“…Calcium (Ca) uptake and cycling are critical for freshwater organisms. 1 Bone and shell formation in freshwater organisms rely on Ca absorption and cycling. 2 The uptake and cycling of Ca ensure the maintenance of appropriate cellular Ca 2+ concentrations, thereby supporting normal metabolic reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Numerous evidence suggested that D. magna was highly sensitive to low Ca concentrations, and field studies demonstrated reduced population growth in zooplankton species under such conditions 52. Laboratory studies further revealed that low-Ca environments led to diminished body size, survival rate, and reproductive capabilities in D. magna 1,53,54. However, previous studies predominantly focused on the end point of accumulation deficiency effects of Ca in the body, while investigations into the kinetics of Ca passage through the intestine were limited 10,13,55.…”
mentioning
confidence: 99%